GNOSTIC VIEW IN CONTEMPORARY ISLAMIC ARCHITECTURE (IN CASE OF ARDALAN) - Hamid, AGHAEI RAD (DIMENSI (Journal of Architecture and Built Environment), 2014)
This paper argues that essentially Nader Ardalan has tried to enrich contemporary architecture of his time with his understanding of traditional Islamic architecture. Consequently, this paper pays attention to Nader Ardalan’s works and thought. This article generally points to the relationship between idea and practice to preserve traditional Islamic architecture and in particular, it demonstrates the influence of the ideas of Ardalan’s book, The Sense of Unity: The Sufi tradition in Traditional Persian Architecture (1974), on his projects. This article particularly concludes that despite the rise of technology of construction and modification of context and eco-social forces which are apparent over the three decades of design, the principles of traditional Islamic architecture can be identified conceptually within Ardalan’s projects to differing degrees.